1999
DOI: 10.1007/s004390050911
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of two distinct 6p deletion syndromes

Abstract: Deletions of the short arm of chromosome 6 are relatively rare, the main features being developmental delay, craniofacial malformations, hypotonia, and defects of the heart and kidney, with hydrocephalus and eye abnormalities occurring in some instances. We present the molecular cytogenetic investigation of six cases with 6p deletions and two cases with unbalanced translocations resulting in monosomy of the distal part of 6p. The breakpoints of the deletions have been determined accurately by using 55 well-map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
135
2
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(149 citation statements)
references
References 35 publications
10
135
2
2
Order By: Relevance
“…13 In addition, chromosome aberrations including 6p25 have been reported together with anterior segment malformations and additional clinical findings. 1,3,14 The FOX-gene FOXC1 is located in the critical IRID1 region and deleted in our patient, and mutations in this gene have been found in familial and isolated cases with anterior chamber anomalies. However, not all families with anterior chamber defects mapped to 6p25 have mutations in the FOXC1 gene, which implies the presence of other genes involved in eye development in the region.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…13 In addition, chromosome aberrations including 6p25 have been reported together with anterior segment malformations and additional clinical findings. 1,3,14 The FOX-gene FOXC1 is located in the critical IRID1 region and deleted in our patient, and mutations in this gene have been found in familial and isolated cases with anterior chamber anomalies. However, not all families with anterior chamber defects mapped to 6p25 have mutations in the FOXC1 gene, which implies the presence of other genes involved in eye development in the region.…”
Section: Discussionmentioning
confidence: 65%
“…Knight et al reported a case with a 6p deletion estimated to 6.4 -8.6 cM, but did not include clinical data beside mental retardation. 4 Davies et al 3 compared the clin- Figure 1 Facial appearance of the patient at age 4 years and 9 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human CAP2 gene is present on chromosome 6, specifically at 6p22.3. Davies et al [34] reported a new interstitial 6p22-24 deletion syndrome after finding several cases with this type of deletion. The patients studied showed various cardiac defects along with other developmental abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…56 Such long-range position effects have previously been suggested for other disorders 57 and interestingly FOXC1 has also been associated with long-range position effects. 58 Some of the missense mutations leading to amino acid substitutions and other types of mutations have been investigated by functional studies and these mutations alter the protein function in varying degrees (Tables 2 -3 and Supplementary Figures 1 -2). Most of the intragenic PITX2 mutations are loss-of-function mutations, which result in defective DNA binding, decreased transactivation capability of downstream genes, or both (Table 2).…”
Section: Foxc1 Defects and Arsmentioning
confidence: 99%